3D electron diffraction of mono- and few-layer MoS2. (July 2021) - Gorelik, Tatiana E.; Nergis, Berkin; Schöner, Tobias; Köster, Janis; Kaiser, Ute
Highlights: 3D ED volume of 2D MoS2 shows relrods with a complex intensity distribution. The intensity distribution within the relrods depends on the number of layers. MoS2 crystals with odd and even number of layers have different symmetry. Number of layers up to 5 can be determined from 3D ED data. Abstract: Mono- and few-layer MoS2 were studied by three-dimensional electron diffraction (3D ED) showing distinctly different symmetry for crystals consisting of odd and even number of layers. Experimentally obtained intensity distributions along the relrods match qualitatively kinematically simulated data. Our findings allow to differentiate unambiguously between 1-, 2-, 3- 4- and 5-layers MoS2 crystals.